Investigation of stoichiometry of oxygen precipitates in Czochralski silicon wafers by means of EDX, EELS and FTIR spectroscopy. (November 2016) - Kot, D.; Kissinger, G.; Schubert, M.A.; Klingsporn, M.; Huber, A.; Sattler, A.
Abstract: In this work, we used EDX, EELS and FTIR spectroscopy to investigate the stoichiometry of oxygen precipitates in Czochralski silicon wafers. The EDX analysis of a plate-like precipitate demonstrated that the composition of the precipitate is SiO1.93 . This result was confirmed by EELS where the characteristic plasmon peak of SiO2 was observed. Additionally, the absorption band of plate-like precipitates at 1223 cm −1 was found in the FTIR spectrum measured at liquid helium temperature. It was demonstrated that this band can only be simulated by the dielectric constants of amorphous SiO2 . Highlights: The thickness of the investigated sample is an important parameter having influence on the intensity of the X-rays. From equation (1), we determined the x values in the EDX probed field which was 1.93. The experimental spectrum can be very well simulated by 5 absorption bands using the dielectric function of amorphous SiO2 .